Study of the superconducting properties of the new intermetallic compound Zr1−xNbxB2. (21st July 2016) - Marques, M D R; Portela, F S; Corredor, L T; Zhang, G; Vanacken, J; Moshchalkov, V V; Correa, L E; Renosto, S T; Cigarroa, O; Machado, A J S; Aguiar, J Albino
Abstract: In this paper we report on the synthesis and the structural, electrical, magnetic and thermal analysis for the new material Zr 1 − x Nb x B 2 (0.01 ≤ x ≤ 0.05). A superconducting transition was observed for all x values studied, despite the non-superconducting matrix ZrB2, which indicates that the superconducting state is induced by the presence of Nb. The results show that the critical temperature increases with Nb content, reaching its maximum ( T c = 8.1 K) for x = 0.04. From the specific heat data we find a Sommerfeld constant of γ = 1.6 mJ molK −2 and a Debye temperature of θ D = 615.5 K. Unconventional behaviors are observed in specific heat dependence with temperature and in H c 1 ( T ) diagram. These behaviors are investigated in C e / T versus T curve, where an upturn appears for T < 2.3 K, and in ln ( C e / γ T c ) versus T c / T dependence, which shows a clear deviation from BCS theory for low temperatures. Also, contrary to the conventional theories we found a positive curvature for temperatures near T c in the lower critical field, besides an upturn around 2.3 K. We suggest that these behaviors possibly arise from multiband superconductivity in Zr 0.96 Nb 0.04 B 2 .